2017
DOI: 10.1590/s0100-736x2017000800020
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia da traqueia e lobação pulmonar de Leopardus pardalis (jaguatirica)

Abstract: RESUMO: A espécie Leopardus pardalis, conhecida popularmente como jaguatirica, é um felino de médio porte com ampla distribuição em território nacional e está incluída na lista de espécies da fauna brasileira ameaçadas de extinção. Este estudo teve como objetivo caracterizar os aspectos macroscópicos e microscópico da traqueia e lobos pulmonares em L. pardalis. As análises foram feitas utilizando cinco exemplares de jaguatirica, sendo dois machos e três fêmeas, adultos, três desses exemplares foram a óbito por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
1
0
2
Order By: Relevance
“…Regarding pulmonary lobation, the classic veterinary literature clarifies the following pattern: Right lung with four lobes: Cranial, caudal, medium, and accessory and left lung divided into two lobes, cranial and caudal [19,20,23]. The results observed in our research are similar to those found in other mammals: Carnivores, such as dogs [31], Leopardus pardalis [38], N. nassua [32,33], and P. cancrivorus [35]; rodents, such as Hydrochoerus hydrochaeris [39]; Xenarthra, such as Myrmecophaga tridactyla [40]; and primates, such as Callithrix penicillata [41]. Although there is great variation in macroscopic and pulmonary lobation characteristics in several species of wild mammals, only phylogenetic studies will be able to show whether there is a pattern for bronchial lobation in different mammalian orders [27].…”
Section: Discussionsupporting
confidence: 86%
“…Regarding pulmonary lobation, the classic veterinary literature clarifies the following pattern: Right lung with four lobes: Cranial, caudal, medium, and accessory and left lung divided into two lobes, cranial and caudal [19,20,23]. The results observed in our research are similar to those found in other mammals: Carnivores, such as dogs [31], Leopardus pardalis [38], N. nassua [32,33], and P. cancrivorus [35]; rodents, such as Hydrochoerus hydrochaeris [39]; Xenarthra, such as Myrmecophaga tridactyla [40]; and primates, such as Callithrix penicillata [41]. Although there is great variation in macroscopic and pulmonary lobation characteristics in several species of wild mammals, only phylogenetic studies will be able to show whether there is a pattern for bronchial lobation in different mammalian orders [27].…”
Section: Discussionsupporting
confidence: 86%
“…The anatomical description of many wild animals is little elucidated in the scientific community and evolves slowly. The anatomy of components of the respiratory system has already been approached in range of animal species such as ocelots ( Leopardus pardalis ) (Schuingues et al, 2017), coatis ( Nasua nasua ) (Oliveira et al, 2011), sloths ( Bradypus variegatus and Choloepus hoffmanni ) (Faro et al, 2015; Vigil‐Esquivel et al, 2021), brown capuchins ( Sapajus apella ) (Leonel et al, 2013) and wild felines (Weissengruber et al, 2002). With regard to giant anteaters, the gross morphology of the upper respiratory system was first investigated in 19th century by Owen (1854).…”
Section: Introductionmentioning
confidence: 99%
“…Diferente das descrições anatômicas da traqueia humana com aproximadamente de 15 a 20 anéis (Testut;Latarjet, 1979) e em gorila (Gorila gorila) a contagem de 17 anéis (Raven, (1950 A morfologia pulmonar do Alouatta belzebul consiste em pulmão direito dividido em: lobo cranial, lobo médio, lobo caudal e lobo acessório (Figura 6), enquanto que o pulmão esquerdo é dividido em: lobo cranial e lobo caudal. É bem semelhante em relação as estruturas pulmonares, como divisão lobar, bronquial e presença de um lobo acessório, quando comparada aos outros primatas neotropicais como sagui-de-tufos-brancos (Callithrix jacchus) (Falcão, et al 2018) e gibões de mão branca, (Hylobates agilis) (Nakakuki S, Akiyoshi E, 1993), e alguns mamíferos silvestres como, Jaguatirica (Leopardus Pardalis) (Schuingues et al, 2017). Research, Society and Development, v. 9, n. 11, e5039119927, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9927 Quando comparados a outras espécies de primatas, os pulmões do Alouatta belzebul, demonstraram bastante similaridade em relação à descrições observadas na literatura, como em Gorila (Gorila gorila) (Nakakuki, 1991), Gibões de mão branca, (Hylobates agilis) (Nakakuki e Akiyoshi, 1993), Macaco comedor de caranguejo (Macaca fascicularis) (Nakakuki, 1994), Sagui-de-tufos-brancos (Callithrix jacchus) (Falcão et al, 2018).…”
Section: Figuraunclassified
“…Quando comparados com outros espécimes, a divisão lobar do Alouatta belzebul, mostrou-se bastante similar em relação a disposição dos lobos em mamíferos domésticos como canídeos, ovinos, bovinos, equídeos e suínos (Dyce et al, 2010), (Cury et al, 2013) e animais silvestres como raposa (Cerdocyon thous) (Dantas et al, 2014) o que difere para jaguatirica (Leopardus Pardalis) (Schuingues, et al, 2017) Research, Society and Development, v. 9, n. 11, e5039119927, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9927 Caudal BM55623 3 2 5 2 3 5 BM55322 2 2 4 2 3 4 BM46182 3 2 5 2 3 4 BM91659 2 2 5 2 3 5 BM49402 3 2 5 2 3 4 BM70990 3 2 4 2 4 5 BM88397 3 2 4 2 4 5 MODA 3 2 5 2 3 5 A ramificação segmentar é semelhante ao descrito em Gibões de mão branca, (Hylobates agilis) (Nakakuki e Akiyoshi 1993), em Gorila (Gorila gorila) (Nakakuki e Akiyoshi 1991), Macaco comedor de caranguejo, (Macaca fascicularis) (Nakakuki 1994), Sagui-de-tufos-brancos (Callithrix jacchus) (Falcão, et al 2018). Em todas ás espécies de primatas estudados não há variação muito grande na quantidade de brônquios segmentares emitidos do brônquio lobar cranial direito, exceto Chimpanzé (Pan troglodyte) (Nakakuki 1992) e Orangotango, (Pomgo pygmaeus) (Nakakuki e Akiyoshi 1991), cuja variação deriva por não apresentar um lobo acessório.…”
Section: Gibões De Mão Branca (Hylobates Agilis)unclassified